Tension Stiffening Behavior of Polypropylene Fiber- Reinforced Concrete Tension Members - Aris Aryanto; Berto Juergen Winata (Journal of Engineering and Technological Sciences, 2021)
This paper focuses on comparing the behavior of RC tension members with and without the addition of polypropylene fibers at various corrosion levels. Eight cylindrical tensile specimens were tested to evaluate their tension-stiffening and cracking behavior. The content of polypropylene fiber added into the concrete mix was the main variable (0.25%, 0.50%, 0.75%, and 1.0% of total volume). The corrosion level was varied from slight (5%), medium (10%) to severe (30%) and, like the other variables, applied only to 1.0% polypropylene fiber-reinforced concrete (PFRC) specimens. The test results showed that the fiber addition significantly increased the tension-stiffening effect but was largely unable to reduce the effect of bond degradation caused by corrosion. Moreover, the addition of polypropylene fibers was able to improve the cracking behavior in terms of crack propagation, as shown by smaller crack spacing compared to the specimen without fiber addition at the same corrosion level.